2016
DOI: 10.3109/08958378.2015.1136715
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inhaled acute ammonia-induced lung injury in rats

Abstract: This study examined acute toxicity and lung injury following inhalation exposure to ammonia. Male Sprague-Dawley rats (300-350 g) were exposed to 9000, 20,000, 23,000, 26,000, 30,000 or 35,000 ppm of ammonia for 20 min in a custom head-out exposure system. The exposure atmosphere, which attained steady state within 3 min for all ammonia concentrations, was monitored and verified using a Fourier transform infrared spectroscopy (FTIR) gas analyzer. Animals exposed to ammonia resulted in dose-dependent increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This observation is consistent with other studies performed in mouse and rat brain endothelial cell lines [63,64], suggesting that the toxic effects of ammonia may be cell-specific. Surprisingly, we show that ammonia pretreatment markedly reduces endothelial cell death in response to TNFα and cycloheximide.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with other studies performed in mouse and rat brain endothelial cell lines [63,64], suggesting that the toxic effects of ammonia may be cell-specific. Surprisingly, we show that ammonia pretreatment markedly reduces endothelial cell death in response to TNFα and cycloheximide.…”
Section: Discussionsupporting
confidence: 93%
“…High‐concentration ammonia exposure can induce the tracheal tissue injury and noncoding RNAs play a crucial role in this process 13 . Study on acute ammonia toxicity in rats found the lung injuries and the significantly increased protein concentration and total cell counts from bronchoalveolar fluid, as well as the increased white blood cells, neutrophils, and platelets from blood following inhalation exposure to ammonia 14 . Many researches have also found that ammonia can induce oxidative stress and cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Personal exposure to ammonia at a certain concentration could cause a strong stimulating and corrosive effect on human eyes, nose, throat, and skin. 3,4 Exposure to ammonia at the concentration of about 20-95 mg/m 3 in the urea fertilizer factory could induce acute respiratory symptoms and acute decline in lung function. 2 Chronic ammonia inhalation could also cause pulmonary fibrosis and interstitial lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…Its widespread usage makes it a common occupational hazard factor in the air of workplace and creates a large potential for worker occupational exposure. Personal exposure to ammonia at a certain concentration could cause a strong stimulating and corrosive effect on human eyes, nose, throat, and skin . Exposure to ammonia at the concentration of about 20‐95 mg/m 3 in the urea fertilizer factory could induce acute respiratory symptoms and acute decline in lung function .…”
Section: Introductionmentioning
confidence: 99%